Farmers' perceptions of and responses to environmental change in southwest coastal Bangladesh. (28th August 2017) - Kabir, Md Jahangir; Cramb, Rob; Alauddin, Mohammad; Roth, Christian; Crimp, Steven
Abstract: Coastal Bangladesh is highly vulnerable to climate change and salinisation; hence, farm‐level adaptation is critically important. Farmers' perceptions of and responses to environmental change were investigated in two villages in Khulna District. Perceived environmental trends included increases in temperature, extreme weather events, soil toxicity, erratic rainfall and scarcity of water for irrigation. Perceptions of climate trends were consistent with measured trends in Khulna. On‐farm adaptation strategies included adjusting planting dates, excavating trenches in rice‐fields, adopting new crops, salinity‐reducing technologies, livestock‐rearing and home‐yard cropping. Non‐farm adaptation strategies included wage employment, short‐term migration and self‐employment. Adaptation was facilitated by income‐earning opportunities, training, and credit, and impeded by lack of access to water, markets, capital, and extension services. Farmers suggested policy support for dissemination of stress‐tolerant cultivars, access to irrigation, and price stabilisation or crop insurance to assist adaptation. While the study shows an impressive degree of awareness and adaptation, external support is needed to increase adaptive capacity.